PENGARUH PENDIDIKAN DAN LATIHAN SERTA KOMPETENSI TERHADAP IMPLEMENTASI SPIP GUNA PENCEGAHAN FRAUD - Hendriani, Susi (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2013)
This study aimed to examine the effect of education and competence as well as theGovernment Internal Control System (SPIP) to the internal control system and itsimplications in the prevention of fraud. Types of data used are primary data derivedfrom respondents answers. The population in this study were all auditors in CentralJava Province Representative BPK as many as 221 people auditor. The analysistechnique used is the SEM technique. Based on the results of research anddiscussion, it can be concluded that: 1) Education SPIP training in fraud preventionefforts directly or through competence and SPIP in government agencies in CentralJava province has not been effective, 2) Effect of Education training, competence,and the prevention of fraud SPIP demonstrate that the government agencies inCentral Java Province, competence and influence SPIP fraud prevention. In contrastwith SPIP training education only it were not so influential to the prevention of fraudin government departments in the province of Central Java, 3) Education Training,SPIP and competence when done together will air indirectly influence the preventionof fraud than if each stood alone.Keywords: education, competence, SPIP, the system of internal control, and fraud